Interaction of time and breastfeeding type on maternal postpartum weight and body fat - Faizatul Ummah; Rini Stiyowati; Dwi Dianita Irawan; Wan Ismahanisa Ismail (Universitas Aisyiyah Yogyakarta, 2026)
Postpartum weight retention and excess adiposity increase the risk of long‑term maternal obesity and cardiometabolic disease, yet evidence on how time and breastfeeding type affect early postpartum weight and body fat trajectories remains limited. This prospective cohort study examined the effect of time and breastfeeding type on changes in maternal postpartum weight and body fat percentage among 34 postpartum mothers (17 exclusively vs. 17 partially breastfeeding) selected through purposive sampling. Breastfeeding data was collected by interview, body weight was measured using a digital scale, and body fat percentage was assessed using skinfold anthropometry at the first week, 1 month, and 3 months postpartum. Data were analyzed using mixed‑design ANOVA. Exclusively breastfeeding mothers showed gradual decreases in body weight and body fat percentage, whereas partially breastfeeding mothers showed increases over the same period (mean body weight 62.58; 61.25; 58.08 kg vs. 66.11; 67.38; 68.66 kg; and mean body fat percentage 31.05%; 29.65%; 27.28% vs. 29.26%; 30.94%; 32.72%). Although there were no significant differences in body weight (p = 0.076) or body fat percentage (p = 0.888) across time points, a significant interaction between breastfeeding time and type was found for both body weight (p < 0.001) and body fat percentage (p < 0.001), indicating different change trajectories between the two groups over time. Exclusive breastfeeding is linked to better postpartum weight and fat loss than partial breastfeeding. A larger sample and longer follow-up study including additional factors (maternal diet, physical activity, stress, and nutritional status during breastfeeding) are recommended.